Analisis Produksi Dan Pendapatan Usahatani Padi Sawah Di Desa Manleten Kecamatan Tasifeto Timur Kabupaten Belu - Terezina Lopes; Yosefina Marice Fallo (AGRIMOR, 2019)
This study aims: 1) To know the general description of wetland rice farming in Manleten Village, Tasifeto Timur District, Belu Regency; 2) Knowing the income of rice paddy farming in Manleten Village, Tasifeto Timur District, Belu Regency. This research has been carried out in Manleten Village, Tasifeto Timur Subdistrict, Belu Regency, from January to September 2018. The method used in this study is a survey method with the type of data used primary data and secondary data, to find out the first purpose descriptive analysis, while for knowing the income of lowland rice farming, namely the difference between revenue and all costs. The results of the study show that rice farming activities go through several stages: 1) nursery; 2) preparation and processing of paddy fields; 3) planting; 4) maintenance; 5) harvest; 6) post-harvest; and 7) marketing. The receipt of lowland rice farming in the village of Manleten ranged from Rp. 18,000,000 to Rp. 137,500,000 with an average of Rp. 57,889,063. The cost of producing paddy rice farming ranged from Rp. 495,470 to Rp. 24,757,700 with an average of Rp. 12,696. 538 the income of wetland rice farming also ranged from Rp 1,820,667 to Rp. 113,774,000 with an average of Rp. 45,192,524.